TEKNIK PEMELIHARAAN DAN PERILAKU RESPON ORANGUTAN KALIMANTAN (PONGO PYGMAEUS MORIOOWEN, 1837) DITAMAN SATWA CIKEMBULAN GARUT - Nawangsari, Ventie Angelia; Mustari, Abdul Haris; Masy'ud, Burhanuddin (Media Konservasi, 2016)
Borneo orangutan is endangered primate species due to the declining of its population in the wild. Its existence required conservation effort, through the exi-situ conservation. Captive management and adaptation in the ex-site effort has to be considered. The objectives of this research was to study captive breeding management and evaluating response of orangutans in Animal Park CikembulanGarut West Java. The research was conducted on March 10-30, 2014. Data of captive breeding management has done by observation such as interview to the worker and literatures study. Orangutan response was observed through an experiment in which the experiment in which different color drees (black, red, blue, and yellow). Orangutan response to color dreeswas assessed bymeasuring the distanceto the observer's response orangutans.The parametersmeasured werepresence or absenceof orangutansactivity responsetotreatment.Orangutan gave positive response to theobserver using red drees. Cage management wasnot ideal, due to lack of quarantine cage and cage enrichment. However, feeding management was considered ideal despite the lack of feed weighing. Health management was not ideal, since there was not any clinic available for sick animals.  Keywords:captive breeding management, orangutan, response